2020
DOI: 10.1007/s13197-020-04456-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of almond genotypes on fatty acid composition, tocopherols and mineral contents and bioactive properties of sweet almond (Prunus amygdalus Batsch spp. dulce) kernel and oils

Abstract: Oil content of almond kernels ranged from 36.7% in the cultivar T12 to 79.0% in genotype T27. The major fatty acid in almond oil is oleic (62.43% in T7-76.34% in T4) followed by linoleic (13.97% in T4-29.55% in T3) and palmitic (4.97% in T2-7.51% inT3). The main tocopherol in almond oil was a-tocopherol (44.25 mg/ 100 g in T25-75.56 mg/100 g in T13) that was 44 folds higher than other tocopherols in the oil. Total tocopherol contents of almond oils ranged between 47.42 mg/100 g (T14) and 80.15 mg/100 g (T16). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 29 publications
5
24
1
Order By: Relevance
“…In the case of paste, although the yield was higher for methanol, the total phenolic content was higher in the extraction with acidified water (Figure 3). Compared with previous studies, the content of total phenols found in this study was lower than that reported in various commercial P. dulcis cultivars (39,40) and higher than that reported in various genotypes of P. amygdalus almond (16). In the case of oil, although the highest yields were found in ethanol and acidified water, the highest total phenol content was found in acetone as a solvent (Figure 3).…”
Section: Solvent Yields and Extraction Of Total Phenolicscontrasting
confidence: 90%
See 3 more Smart Citations
“…In the case of paste, although the yield was higher for methanol, the total phenolic content was higher in the extraction with acidified water (Figure 3). Compared with previous studies, the content of total phenols found in this study was lower than that reported in various commercial P. dulcis cultivars (39,40) and higher than that reported in various genotypes of P. amygdalus almond (16). In the case of oil, although the highest yields were found in ethanol and acidified water, the highest total phenol content was found in acetone as a solvent (Figure 3).…”
Section: Solvent Yields and Extraction Of Total Phenolicscontrasting
confidence: 90%
“…On the other hand, the antioxidant activity values found in pasta (Figures 5, 6) are lower than those reported in P. serotina Ehrh. (7) and P. amygdalus L. (16,43), but higher than those reported by Summo et al (11) in P. dulcis. Finally, in the case of oil, the antioxidant activity values obtained in this research (Figures 5, 6) were similar to those reported in P. serotina by Lu-Martínez et al (25) and higher than those reported in P. dulcis by Miraliakbari (42).…”
Section: Antioxidant Activity Evaluationsmentioning
confidence: 57%
See 2 more Smart Citations
“…The concentrations of total phenolic content in the analyzed almond oils present a value of 138 mg/kg. Other studies by Rabadán et al and Ozcan et al [12,13] have shown values of phenol content ranging from 18.53 mg/kg to 237 mg/kg.…”
Section: Total Phenols and Tocopherol Content Of Almond Oilsmentioning
confidence: 84%